The Effect of Financial Self-Efficacy and Financial Knowledge on Financial Management Behavior - Asmin, Erny Amriani; Ali, Muhammad; Nohong, Mursalim; Mardiana, Ria (Golden Ratio of Finance Management, 2021)
This study aims to determine financial knowledge and financial self-efficacy on financial management behavior. All respondents who were sampled in this study were young entrepreneurs who started a business from the beginning as many as 85 respondents, taking samples using a non-probability sampling method with purposive sampling technique. The data is processed using Warp-Pls 7.0 based on multiple regression. Financial self-efficacy and financial knowledge have a positive and significant contribution to financial management Behavior for young entrepreneurs. The results of this study have managerial implications that the government's attention is essential in providing facilities and infrastructure, favorable regulations for SMEs by creating an excellent entrepreneurial climate and facilitating the adoption of information technology so that SMEs can be technology literate. In addition, the relevant government, in this case for SME entrepreneurs' existence helps the government to succeed in development, especially in the economic field, and reduce unemployment. Based on our study states financial self-efficacy and financial knowledge have a positive and significant effect on financial management behavior for young entrepreneurs. Both, play a vital role in helping to build confidence in financial planning and management knowledge, understanding, and being able to overcome all business risks to achieve the expected success.